Analysis of food intakein pre-game professional football players - Brant, Amanda Cristine Assis (2012)
Objective: To assess the adequacy between the nutritional recommendation and the dietary patterns of pre-game intake of macronutrients in professional footballplayers. Materials and Methods: 18 male athletes with average age 24.66 ±3.1 years (21-31) belonging to the elite of São Paulo footballwere evaluated. Body composition was determined by measuring skinfolds, weight and height measured using scales and stadiometer and the measurement of the caloric intake was obtained through food survey. Data analysis used the Excel 2007 program. Results and Discussion: There was an average pre-game calorie intake of 3099.83 ±893.91 kcal, corresponding to the following intakes: carbohydrate 51.14 ± 0.09%, lipids 26.45 ±0.075% and protein 22.40 ±0.04%. The number of meals eaten and their fractionation made by most of the athletes are awkward to the needs required by the game so that there is performance optimization. Conclusion: The pre-game calorie intake is insufficient, with low-carb, high protein intake, while diets suit in lipid levels. It is vital that there is an effective nutritional intervention to correct theplayers' eating behaviors.